The (New) roles of prototypes during the co-development of digital product service systems - Kleinsmann, Maaike; ten Bhömer, Martijn (National Taiwan University of Science and Technology, 2020)
This paper investigates different roles that prototypes play during the development of digital Product Service Systems (PSSs). A literature review reveals that prototyping supports designers during the design process, as well as during knowledge sharing processes with stakeholders. To create a better understanding of these two co-existing roles of prototyping, we executed a research-through-design project in the healthcare domain. This design project was centred around the development of four different prototypes that the designer sequentially developed. A major input into the design process was co-reflection sessions between the designer and different stakeholders. We analysed the prototyping process and the co-reflection sessions. Moreover, we executed a conversational analysis to understand the actual knowledge sharing processes between the designer and the different stakeholders. The results present a detailed overview of the different (co-existing) roles of the prototypes. We distinguished two new types of prototypes which were both related to the development of the intangible aspects of the digital PSS: (1) service interface prototrial aimed at exploring several options for detailing the different intangible aspects of the digital PSS, and (2) service provotype to stimulate collaborative creation of the intangible aspects of the digital PSS in an early stage.